Risk and protective factors for nonsuicidal self-injury among adolescents: a latent profile analysis - He, Yunfeng; Kong, Yaxin; Ji, Tianyuan; Tao, Ruoge; Ge, Liping; Yuan, Feng (Frontiers in Psychiatry, 2025)
IntroductionDespite the longstanding interest in the factors influencing nonsuicidal self-injury (NSSI), less attention has been paid to how risk and protective factors interact to influence adolescents' NSSI behaviors. NSSI is a serious psychological crisis with complex etiology that is usually not triggered by a single chance event. Therefore, assessing NSSI based on risk factors alone is inherently inaccurate. In order to provide a more accurate and comprehensive risk assessment framework, we explored the specific patterns of combinations of risk and protective factors within intra-individual and environmental of adolescents involved in NSSI.Methods1091 participants were evaluated on six indicators: depression, emotion regulation, regulatory emotional self-efficacy, resilience, family functioning, and social support.ResultsThe results showed three latent profiles: low risk-high protection (30.62%), medium risk-medium protection (58.20%), and high risk-low protection (11.18%). Compared to low risk-high protection, adolescents in medium risk-medium protection (OR = 2.49) and high risk-low protection (OR = 11.46) were significantly associated with increased odds of experiencing NSSI.DiscussionThe findings suggest that we should focus our prevention efforts on a group of adolescents with high-risk-low-protective characteristics to effectively reduce the incidence of NSSI behaviors by enhancing their protective factors or reducing their risk factors.